Evidence of subgroups in smokers as revealed in clinical measures and evaluated by neuroimaging data: a preliminary study. (8th March 2018) - Ding, Xiaoyu; Salmeron, Betty Jo; Wang, Jamei; Yang, Yihong; Stein, Elliot A.; Ross, Thomas J.
Abstract: To date, fractionation of the nicotine addiction phenotype has been limited to that based primarily on characteristics of cigarette use, although it is widely appreciated that a variety of individual factors are associated with tobacco use disorder. Identifying subtypes of tobacco use disorder based on such factors may lead to better understanding of potential treatment targets, individualize treatments and improve outcomes. In this preliminary study, to identify potential subgroups, we applied hierarchical clustering to a broad range of assessments measuring personality, IQ and psychiatric symptoms, as well as various environmental and experiential characteristics from 102 otherwise healthy cigarette smokers. The identified subgroups were further compared on various resting‐state fMRI measures from a subset ( N  = 65) of individuals who also underwent resting‐state fMRI scanning. The clustering dendrogram indicated that smokers can be divided into three subgroups. Each subgroup had unique clinical assessment characteristics. The division yielded imaging differences between subgroups in the supplementary motor area/middle cingulate cortex and the cuneus. Regression analyses showed that amplitude of low frequency fluctuations in the supplementary motor area/middle cingulate cortex differed between groups and were negatively correlated with the Toronto Alexithymia Scale subscale Difficulty Describing Feelings. Abstract : We applied hierarchical clustering to a broad range of clinical measures to identify subtypes of tobacco use disorder. Smokers can be divided into three subgroups with unique clinical assessment characteristics in each subgroup. The division yielded imaging differences between subgroups in the supplementary motor area/middle cingulate cortex and the cuneus.